KOORDINASI KERJA FRONT OFFICE DEPARTEMENT DENGAN HOUSKEEPING DI HOTEL THE ZURI PEKANBARU - Jamil, Ary Irfan Noor; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the work coordination of the Front Office Department with Housekeeping at The Zuri Hotel Pekanbaru. There is still miscommunication in the form of coordination between the front office department and housekeeping, but it can still be improved. The factors that influence work coordination between these departments have gone quite well, while the inhibiting factor in work coordination between departments is the form of communication between departments. To solve this problem, this research uses a qualitative method using four key informants as sources, namely a Front Office Supervisor, a Housekeeping Supervisor, a Front Desk Agent, and a Room Attendant. In collecting data, the author used interview and documentation techniques. This research uses a descriptive approach where this research explains in detail about Front Office Work Coordination with Housekeeping at The Zuri Pekanbaru Hotel. Based on the results of the research that has been carried out, it is revealed that coordination between the Front Office and Housekeeping has been going well, but still needs to be improved. Keywords: Coordination, Front Office, Housekeeping.